The Effect of the Uncariae Ramulus et Uncus on the Regeneration Following CNS Injury - Lee Jin-Goo; Park Hyoung-Jin; Kim Dong-Woong; Song Bong-Keun (Korean Pharmacopuncture Institute, 2009)
Objective : Following central nervous system(CNS) injury, inhibitory influences at the site of axonal damage occur. Glial cells become reactive and form a glial scar, gliosis. Also myelin debris such as MAG inhibits axonal regeneration. Astrocyte-rich gliosis relates with up-regulation of GFAP and CD81, and eventually becomes physical and mechanical barrier to axonal regeneration. MAG is one of several endogenous axon regeneration inhibitors that limit recovery from CNS injury and disease. It was reported that molecules that block such inhibitors enhanced axon regeneration and functional recovery. Recently it was reported that treatment with anti-CD81 antibodies enhanced functional recovery in the rat with spinal cord injury. So in this current study, the author investigated the effect of the water extract of Uncariae Ramulus et Uncus on the regulation of CD81, GFAP and MAG that increase when gliosis occurs. Methods : MTT assay was performed to examine cell viability, and cell-based ELISA, western blot and PCR were used to detect the expression of CD81, GFAP and MAG. Then also immunohistochemistry was performed to confirm in vivo. Results : Water extract of Uncariae Ramulus et Uncus showed relatively high cell viability at the concentration of 0.05%, 0.1% and 0.5%. The expression of CD81, GFAP and MAG in astrocytes was decreased after the administration of Uncariae Ramulus et Uncus water extract. These results was confirmed in the brain sections following cortical stab injury by immunohistochemistry. Conclusion : The authors observed that Uncariae Ramulus et Uncus significantly down-regulates the expression of CD81, GFAP and MAG. These results suggest that Uncariae Ramulus et Uncus can be a candidate to regenerate CNS injury.